Etika Bisnis Islam Perspektif Al-Ghazali dalam Era Transformasi Digital: Analisis Relevansi pada Platform Shopee - Mar’atus Solikhah; Yoiz Shofwa Shafrani; Timbang Apit Afifah (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2026)
The digital transformation of e-commerce has dramatically reshaped Indonesia’s business landscape, with transaction values projected to reach USD 80 billion by 2025. Nevertheless, this rapid expansion has simultaneously produced critical ethical challenges, including price manipulation, exploitation of personal data, and structural injustice that disadvantages MSME actors. This study aims to analyze the relevance of Islamic business ethics norms from Al-Ghazali’s perspective within the context of the Shopee platform and to formulate applicable strengthening strategies. Utilizing a qualitative method through a literature-based approach examining Al-Ghazali’s works and 45 contemporary studies (2015–2025), this research investigates four fundamental principles of Islamic business ethics: mashlahah (public benefit), niyyah (sincere intention), sidq (honesty), and ‘adl (justice). The findings reveal that the implementation of these principles through features such as rating systems, product reviews, and dispute-resolution centers can enhance consumer protection by up to 65%. However, significant obstacles remain, including uneven product transparency (40%), misuse of reviews (15–20%), and the dominance of profit-driven motives (70%). The study proposes five key strategic recommendations: digital ethics education, AI-Blockchain-based verification systems, integration of mashlahah into recommendation algorithms, multi-stakeholder collaboration, and the development of an Islamic Business Ethics Index (IBEI). Consistent implementation of Al-Ghazali’s ethical principles is expected to foster an e-commerce ecosystem that is equitable, transparent, and oriented toward collective welfare.